Diffusion MRI findings in patients with extensive and minimal post-concussion symptoms after mTBI and healthy controls: a cross sectional study. (2nd January 2018) - Næss-Schmidt, Erhard Trillingsgaard; Blicher, Jakob Udby; Tietze, Anna; Rask, Charlotte Ulrikka; Svendsen, Susanne Wulff; Schröder, Andreas; Thastum, Mille Møller; Tuborgh, Astrid Høeg; Frederiksen, Oana-Veronica; Østergaard, Leif; Eskildsen, Simon Fristed; Hansen, Brian; et al.
ABSTRACT: Primary objectives : We hypothesized that the microstructure of the corpus callosum, thalamus and hippocampus, as measured with diffusion and Mean of the Kurtosis Tensor (MKT) MRI, differs between healthy subjects and patients with extensive and minimal post-concussion symptoms (PCS) and that MKT measures correlate with PCS severity and self-reported cognitive symptoms. Research design : A cross-sectional study comparing patients with extensive PCS and patients with minimal PCS 2–5 months after mild traumatic brain injury (mTBI) with each other and with an external healthy control group. Methods and procedures : Diffusion MRI was obtained in 25 patients with extensive PCS and in 25 patients with minimal PCS as measured by the Rivermead Post-concussion Symptoms Questionnaire. The patients were matched on age, sex and time since accident. Data from an external healthy control group (n = 27) was included. Main outcome and results: There was no difference in MKT between the two groups with mTBI and no correlation between MKT and PCS. There was no difference between the three groups in other diffusion measures. Conclusions : Our results did not point to microstructural changes in the corpus callosum, thalamus and hippocampus in relation to PCS after mTBI.